2018
DOI: 10.3390/ijms19020443
|View full text |Cite
|
Sign up to set email alerts
|

Indole-3-Acetic Acid Biosynthesis Pathways in the Plant-Beneficial Bacterium Arthrobacter pascens ZZ21

Abstract: Arthrobacter pascens ZZ21 is a plant-beneficial, fluoranthene-degrading bacterial strain found in the rhizosphere. The production of the phytohormone indole-3-aectic acid (IAA) by ZZ21 is thought to contribute to its ability to promote plant growth and remediate fluoranthene-contaminated soil. Using genome-wide analysis combined with metabolomic and high-performance liquid chromatography-mass spectrometry (HPLC-MS) analyses, we characterized the potential IAA biosynthesis pathways in A. pascens ZZ21. IAA produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(84 citation statements)
references
References 58 publications
1
72
0
11
Order By: Relevance
“…The results showed that most of the isolates could synthesize IAA, but their production rates were quite different. This variation is due to the different synthetic pathways, key genes and regulatory strategies of different bacteria [30]. Bacteria isolated from the rhizosphere of soybean and rice have been shown to produce 10.54 to 84.72 mg/kg IAA [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that most of the isolates could synthesize IAA, but their production rates were quite different. This variation is due to the different synthetic pathways, key genes and regulatory strategies of different bacteria [30]. Bacteria isolated from the rhizosphere of soybean and rice have been shown to produce 10.54 to 84.72 mg/kg IAA [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Although not as common as that in growth‐promoting bacteria, auxin has been shown to be produced by various beneficial fungi to promote plant root growth and biomass (Li et al, ; Sardar & Kempken, ; Zhang, Gan, & Xu, ), for example, the free‐living beneficial fungus T. virens and T. atroviride promote lateral root growth in Arabidopsis , and the growth‐promoting effect is reduced in mutants that are defective in auxin signalling and transport. The auxin‐related compounds IAA, indole‐3‐acetaldehyde, and indole‐3‐ethanol have been detected in the supernatant of Trichoderma virens and Trichoderma atroviride liquid cultures upon the addition of tryptophan (Contreras‐Cornejo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although not as common as that in growth-promoting bacteria, auxin has been shown to be produced by various beneficial fungi to promote plant root growth and biomass (Li et al, 2018;Sardar & Kempken, 2018;Zhang, Gan, & Xu, 2019), for example, the free-living Transcript levels of genes identified in (a) were significantly upregulated after Arabidopsis exudate treatment. RNA was extracted from F. oryzae hypha and spores at 7 days after cultivation with or without the addition of Arabidopsis (At) exudate, and the transcript levels were determined by quantitative RT-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, P. aeruginosa, P. putida and P. fluorescens can modulate root system architecture through an auxin signaling response mediated by cyclodipeptides [4,18]. Bacterial IAA synthesis mainly depends on tryptophan (Trp) via five distinct pathways including indole-3-acetamide (IAM), indole-3-acetonitrile (IAN), indole-3-pyruvic acid (IPyA), tryptamine (TAM) and tryptophan side-chain oxidase (TSO) pathways [19][20][21]. Some bacterial VOCs such as 2,3-butanediol, 3-hydroxy-2butanone, 2-pentylfuran, N,N-dimethyl-hexadecanamine, carbon dioxide (CO 2 ), 13-tetradecadien-1-ol, 2-butanone and 2-methyl-n-1-tridecene promote plant growth and modulate root system architecture.…”
Section: Introductionmentioning
confidence: 99%